Comparison of New Technology Integrated and Nonintegrated Arterial Filters Used in Cardiopulmonary Bypass Surgery: A Randomized, Prospective, and Single Blind Study - AK, KORAY; ARSAN, SİNAN (HINDAWI LTD, 2013)
Background. Innovative cardiopulmonary bypass (CPB) settings have been developed in order to integrate the concepts of surface-coating, blood-filtration, and miniaturization. Objectives. To compare integrated and nonintegrated arterial line filters in terms of peri-and postoperative clinical variables, inflammatory response, and transfusion needs. Material and Methods. Thirty-six patients who underwent coronary bypass surgery were randomized into integrated (Group In) and nonintegrated arterial line filter (Group NIn) groups. Arterial blood samples for the assessments of complete hemogram, biochemical screening, interleukin-6, interleukin-2R, and C-reactive protein were analyzed before and after surgery. Need for postoperative dialysis, inotropic therapy and transfusion, in addition to extubation time, total amount of drainage (mL), length of intensive care unit, and hospital stay, and mortality rates was also recorded for each patient. Results. Prime volume was significantly higher and mean intraoperative hematocrit value was lower in Group NIn, but need for erythrocyte transfusion was significantly higher in Group NIn. C-reactive protein values did not differ significantly except for postoperative second day's results, which were found significantly lower in Group In than in Group NIn. Conclusion. Intraoperative hematocrit levels were higher and need for postoperative erythrocyte transfusion was decreased in Group In.
Keywords: INFLAMMATORY RESPONSE; CARDIAC-SURGERY; ACTIVATION; PLATELET; HEMATOCRIT; REDUCTION; IMPACT; ADULT